Advantage of conductive materials on interspecies electron transfer-independent acetoclastic methanogenesis: A critical review. (1st December 2021) - Xiao, Leilei; Lichtfouse, Eric; Senthil Kumar, P.
Graphical abstract: Highlights: Biomethane production affected by conductive materials from mechanism to application. Methane production by CO2 bioconversion and acetate dismutation are detailed compared. Acetoclastic methanogenesis mediated by conductive materials is reviewed for the first time. Advantages of CMs were summarized for enhancing CH4 production independent of DIET. Abstract: Fossil-fuel overuse and global warming are calling for new techniques to provide sustainable fuels. Biomethane can be produced by anaerobic digestion of organic waste, yet microbial mechanisms involved are still debated. Traditionally, reduction of carbon dioxide (CO2 ) to methane (CH4 ) is commonly explained by interspecies electron transfer, i. e., direct interspecies electron transfer (DIET)-based CO2 reduction or mediated interspecies electron transfer (MIET)-based CO2 reduction. For DIET-based CO2 reduction, or DIET-CO2 reduction, where electrons are provided by electricigens and transferred to methanogenic archaea to complete CO2 reduction for methane production. Methanogenesis is also executed and facilitated by acetoclastic methanogenesis in the presence of conductive materials, as evidenced recently. Here we compare DIET-CO2 reduction and acetoclastic methanogenesis mediated by conductive materials. In the past decade, DIET-CO2 reduction is considered as the backbone for methane production strategy in anaerobic engineering digestion. But increasing evidences propose the importance of acetoclastic methanogenesis strengthened by exogenous media. DIET-based CO2 reduction has been extensively reviewed. Herein, we conclude the diverse microbial mechanisms affected by conductive materials to improve potential acetoclastic methanogenesis for the first time. Increasing electron transfer in methanogenic archaea and/or between bacteria and methanogens, microbial immobilization, pH buffering capacity, providing metal ions, reducing toxicity, regulation of oxidation-reduction potential are detailed reviewed. Possible future application based on acetotrophic methanogens is suggested via conductive materials in anaerobic digestion and natural ecological environment management.